The Impact of Drug Abuse on Families and Society (Literature Review) - Manurung, Lengsi (PT. Hafasy Dwi Nawasena, 2024)
Drug abuse poses a significant challenge to families and society, manifesting in various detrimental effects. Within families, substance abuse can lead to emotional distress, financial strain, and a breakdown of trust and relationships. It often results in neglect or abuse of children, creating an unstable home environment that hampers the psychological and emotional development of young family members. Additionally, drug abuse can lead to domestic violence and an increase in healthcare and legal issues for the family. On a societal level, drug abuse contributes to increased healthcare costs, loss of productivity, and higher crime rates. The burden on public health systems grows as more individuals require medical treatment for addiction and related health complications. Economically, businesses suffer from decreased productivity and higher absenteeism among employees who struggle with substance abuse. Crime rates tend to escalate as individuals may engage in illegal activities to fund their addiction, which strains law enforcement and judicial systems. Social services also face increased pressure as they work to support affected families and individuals. Efforts to combat drug abuse require comprehensive strategies that include prevention, education, treatment, and rehabilitation programs. Support systems for families, improved access to mental health services, and community-based interventions are crucial to mitigating the impact of drug abuse. By addressing the root causes and providing robust support mechanisms, it is possible to alleviate the profound effects of drug abuse on both families and society.